INFLUENCE OF WINTER WHEATAND REPEATED OILSEEDS IN COTTON CROP ROTATION ON THE AGROPHYSICAL PROPERTIES OF THE SOIL OF SURKHANDARYA REGION - Tadjiev Mardankul; Tadzhiev Karim Mardanakulovich; Danabaev Abdimurad Berdiyevich; Najmiddin Narbayevich (Utilitas Mathematica, 2025)
As a result of agricultural science, it is established that the intensity of plant development and the height of the crop largely depends on the physical properties of the soil. In recent years, the agricultural literature has increasingly focused on studying the physical properties of soil. With the growth of chemicalization, land reclamation and mechanization, the agrophysical state of the soil becomes one of the most important factors determining the level of yield. The physical properties of the soil are especially insignificant in the conditions of irrigated agriculture. High effective soil fertility is largely created by the favorable addition of the soil layer, which determines its physical properties. The main physical properties of the soil include its specific and volumetric mass, porosity, structure, which determine the water-air and thermal properties of the soil, the activity of microbiological processes, and the nutritional conditions of cultivated plants. The research is aimed at studying the soil fertility in monoculture of cotton and in various schemes of cotton crop rotations. Cpossessionhumus in the soil B.The determination of the nitrate form of nitrogen in these soils was carried out by the well-known Grandwald-Liege method, which can be used to most simply and accurately determine the amount of nitrate nitrogen in the soil. Determination of the total nitrogen content in the soil was determined by the method of J.Kjeldahl, determination of mobile mineral forms of phosphorus and potassium was determined by the Machigin method. Theexperimental data were processed according , using the computer program. Agrophysical, agrochemical and microbiological properties of the soil were determined by the Soyuznikha Institute method. Soil volume mass, humidity, and water permeability were determined by the Soyuznikha Institute method. Repeated, intermediate and green manure crops in the cotton crop rotation enrich the soil with organic substances and contribute to improving the agrophysical and agrochemical properties of the soil and reducing weed infestation by 1.9-2.0 times, and the incidence of cotton wilt by 1.8-2.0 times, increasing the yield of cotton by 4.5-5.5 c / ha, reducing the volume mass by 0.08-0.09 g/, and an increase in humus by 0.09-0.12% compared to the control. The main novelty of the work is the first study of changes in soil fertility in the southern desert zone on takyrov-like low-humus soils in the south of Uzbekistan. In conclusion, it can be noted that annual and long-term predecessors in the cotton crop rotation and sowing of repeated, intermediate crops have a positive effect on the agrophysical properties of the soil in comparison with a monoculture without cotton fertilizers and only mineral fertilizers.